2019
DOI: 10.1111/ecc.13145
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sex, age and spiritual well‐being scores on the EORTC QLQ‐SWB32 for patients receiving palliative care for cancer: A further analysis of data from an international validation study

Abstract: Objective The EORTC QOL Group has recently completed the cross‐cultural development and validation of a standalone measure of spiritual well‐being (SWB) for cancer patients receiving palliative care: the EORTC QLQ‐SWB32. The measure includes four scales: Relationships with Others, Relationship with Self, Relationship with Someone or Something Greater, and Existential, plus a Global‐SWB item. This paper reports on further research investigating relationships between sex, age and SWB for patients receiving palli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 30 publications
5
25
5
Order By: Relevance
“…The primary aim of our main study was to explore the structure and validity of a Croatian version of the SWB32 with patient participants in Croatia. We found that this measure was comprehensible and acceptable to all participants, with quantitative findings broadly equivalent to those found in the international study with palliative patients [8], Median values of scale scores in our study were mostly consistent with those in other published studies [8,12,13,19]. For each of the four multi-item scales, the Cronbach's alpha coefficient was above the threshold of 0.6.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The primary aim of our main study was to explore the structure and validity of a Croatian version of the SWB32 with patient participants in Croatia. We found that this measure was comprehensible and acceptable to all participants, with quantitative findings broadly equivalent to those found in the international study with palliative patients [8], Median values of scale scores in our study were mostly consistent with those in other published studies [8,12,13,19]. For each of the four multi-item scales, the Cronbach's alpha coefficient was above the threshold of 0.6.…”
Section: Discussionsupporting
confidence: 89%
“…The secondary aim of our study was to investigate known-group comparisons, examining associations between participants' socio-demographic characteristics and clinical parameters and their scores on the SWB32 scales. We found statistically significant differences for several of our study variables, but, like the international SWB32 validation study [19], we found no differences for marital status, in contrast to other studies with other SWB measures [33,34], although it should be noted that the SWB32 and these measures have distinct conceptualisations of SWB [20], and that these studies were conducted in the USA, so their findings may reflect specific geo-cultural effects.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Contrary to this present study, Chochinov's dignity conservatory repertoire is neither gender-specific nor specifically based on experiences of older women with incurable cancer living at home (Chochinov et al, 2002). Previous studies have shown that gender and diagnosis may affect existential well-being as well as influence the number of physical and psychological problems when nearing end-of-life (Rohde et al, 2019;Vehling & Mehnert, 2014). Since these perspectives may be relevant to the experiences of dignity, we believe this present study adds to the body of knowledge through its gender perspective and the specific focus on older women with incurable cancer living at home .…”
Section: Discussioncontrasting
confidence: 75%